The Effect of Extended Hydroxychloroquine in Intensive Care Managementof Covid 19 on Survival and Costs - (:unkn) unknown (My University, 2020)
INTRODUCTION: There is a broad spectrum of action against most coronaviruses and especially viruses, including SARS-CoV-2. While the hydroxychloroquine treatment recommendation in the national treatment guidelines was 5 days at the beginning of the pandemic, it was recommended as 10 days in cases where the clinic deteriorated under hydroxychloroquine treatment since 14 April. In this retrospective, observational, single-center study, it was aimed to reveal the effect of hydroxychloroquine treatment duration on the day of hospitalization, mechanical ventilation requirement, duration, survival and cost in patients with COVID-19 in intensive care unit.METHODS: Following the approval of the Ethics Committee, the data of the first 50 patients (Group 1) who received hydroxychloroquine for 5 days and the first 50 patients (Group 2) who received 10 days were included in the study. Patients' age, gender, additional diseases, COVID-19 testings, hydroxychloroquine treatment days, invasive mechanical ventilator requirement and duration, intensive care hospitalization day, mortality and costs were recorded.RESULTS: The duration of hospitalization in patients in group 2 was longer than group 1 (9,4 days vs 13,8 days, p=0<0001). There was no difference between the groups in terms of mortality (68%, 62%, respectively, p=0.383). The cost of intensive care unit hospitalization was higher in Group 2.DISCUSSION AND CONCLUSION: In this retrospective observational study, it was found that 10 days of treatment intake did not affect the need for mechanical ventilator and mortality, while extending the intensive care hospitalization period and significantly increasing its cost.

GİRİŞ ve AMAÇ: Hidroksiklorokin, çoğu koronavirüse ve özellikle SARS-CoV-2 dahil olmak üzere virüslere karşı geniş bir etki yelpazesi vardır. Ulusal tedavi kılavuzlarındaki hidroksiklorokin tedavi önerisi pandeminin başlangıcında 5 gün iken, 14 Nisan'dan itibaren hidroksiklorokin tedavisi altında kliniğin kötüleştiği durumlarda 10 gün olarak önerilmiştir. Bu retrospektif, gözlemsel, tek merkezli çalışmada, yoğun bakımda COVID-19 ile izlenen hastalarda hidroksiklorokin tedavi süresinin hastanede kalış günü, mekanik ventilasyon gereksinimi, süresi, sağkalıma ve maliyet üzerine etkisinin ortaya çıkarılması amaçlanmıştır. YÖNTEM ve GEREÇLER: Etik Kurul onayının ardından 5 gün süreyle hidroksiklorokin alan ilk 50 hastanın (Grup 1) ve 10 gün alan ilk 50 hastanın (Grup 2) verileri çalışmaya dahil edildi. Hastaların yaşı, cinsiyeti, ek hastalıkları, COVID-19 testleri, hidroksiklorokin tedavi günleri, invazif mekanik ventilatör ihtiyacı ve süresi, yoğun bakımda yatış günü, mortalite varlığı ve maliyetleri kaydedildi. BULGULAR: Grup 2'deki hastaların hastanede kalış süresi grup 1'den daha uzundu (9,4 güne karşı 13,8 gün, p = 0 <0001). Mortalite açısından gruplar arasında fark yoktu (sırasıyla % 68, % 62, p = 0.383). Grup 2'de yoğun bakımda yatış maliyeti daha yüksekti. TARTIŞMA ve SONUÇ: Bu retrospektif gözlemsel çalışmada 10 günlük tedavi alımının mekanik ventilatör ihtiyacını ve mortaliteyi etkilemediği, yoğun bakımda yatış süresini uzattığı ve maliyetini önemli ölçüde artırdığı ortaya konulmuştur.
Covid 19'un Yoğun Bakım Yönetiminde Uzatılmış Hidroksiklorokinin Sağkalım ve Maliyetler Üzerindeki Etkisi